Solving the Problem of Determining an Intelligent Decision Making System in the Industrial Safety Management System - Rasulov, S.R.; Solod, S.A.; Yagubov, E.Z.; Abdullayeva, N.A. (Herald of Azerbaijan Engineering Academy, 2025)
The article considers the problem of determining an intelligent decision making and management system in the occupational safety management system at industrial enterprises based on game theory. For clarity and simplicity of presentation, we will assume that each of the parties involved in the conflict has two management strategies and for this reason it is possible to limit the solution of the problem on the basis of matrix and bimatrix games. The problem of determining the type of antagonism between the players and determining the goals of the systems, clarifying their interests is considered. The basic control subsystem is described, which will be described by a weight function, its parameters depend on the solution of the game problem and the choice of the intelligent control subsystem for the purpose of the system and the corresponding indicators and optimization criteria.